2003
DOI: 10.1074/jbc.m207454200
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Pancreatic Acinar Cell Calcium Signaling after Pancreatic Duct Obstruction

Abstract: Intracellular Ca2؉ -changes not only participate in important signaling pathways but have also been implicated in a number of disease states including acute pancreatitis. To investigate the underlying mechanisms in an experimental model mimicking human gallstone-induced pancreatitis, we ligated the pancreatic duct of Sprague-Dawley rats and NMRI mice for up to 6 h and studied intrapancreatic changes including the dynamics of [ influx in response to secretagogue stimulation. Serum pancreatic enzyme elevation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 41 publications
6
72
0
Order By: Relevance
“…These findings were parallel with those found previously in different species of rabbit 7,10,14 . The presence of main pancreatic duct in domestic cats was similarly recorded in the other laboratory species such as mice, rats, guinea pigs and hamster 9,[15][16][17] . Similarly to the cat pancreas, the main duct was recorded in sheep and goats but differently these animals have also accessory duct 18 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings were parallel with those found previously in different species of rabbit 7,10,14 . The presence of main pancreatic duct in domestic cats was similarly recorded in the other laboratory species such as mice, rats, guinea pigs and hamster 9,[15][16][17] . Similarly to the cat pancreas, the main duct was recorded in sheep and goats but differently these animals have also accessory duct 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal, prolonged, global elevations of [Ca 2ϩ ] i initiate premature intracellular digestive enzyme activation and vacuolization, early changes of pancreatic acinar cell injury, both in vitro within isolated living pancreatic acinar cells exposed to hyperstimulation (11,12), TPG (11), or bile salts (19,20) and in vivo within the duct-obstructed pancreas (21). The abnormal [Ca 2ϩ ] i elevations may induce Ca 2ϩ release from zymogen granules, which prompts unfolding and premature activation of digestive enzymes (11,32).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, hyperstimulation elicits a sustained, global [Ca 2ϩ ] i rise that in turn induces pronounced premature intracellular digestive enzyme activation and vacuolization (11), nuclear factor B activation (16), cytokine expression (17,18), and acinar cell death (1,17), characteristic changes of acute pancreatitis. Similar changes are induced by naturally occurring bile salts (19,20) and pancreatic duct obstruction (21), which also induce acute pancreatitis.…”
mentioning
confidence: 92%
“…27 Furthermore, supra-maximal concentrations of CCK-induced elevation of baseline Ca 2 þ in isolated pancreatic acinar cells which was strongly linked to premature intracellular activation of trypsinogen, the hallmark of acute pancreatitis, 2,3 an effect that may involve activation of the vacuolar ATPase. 28 This action to raise cytosolic Ca 2 þ is shared by other diverse pathological stimuli that cause pancreatic injury, including non-oxidative ethanol metabolites, 11,12 duct ligation 29 and bile acids. [30][31][32] In addition, recent evidence has shown that the enzyme phosphatidylinositol 3-kinase (PI3K) mediates prolonged elevations of cytosolic Ca 2 þ , under conditions of agonist stimulation, via an inhibitory action on the sarcoendoplasmic reticulum Ca 2 þ ATPase (SERCA) pump; 33 the PI3K system has been implicated in the development of acute pancreatitis since pharmacological inhibition or knockout of this enzyme was protective in experimental animal models.…”
mentioning
confidence: 99%